2002
DOI: 10.1103/physrevb.65.064506
|View full text |Cite
|
Sign up to set email alerts
|

Infrared and optical properties of pure and cobalt-dopedLuNi2B2C

Abstract: We present optical conductivity data for Lu(Ni1−xCox)2B2C over a wide range of frequencies and temperatures for x=0 and x=0.09. Both materials show evidence of being good Drude metals with the infrared data in reasonable agreement with dc resistivity measurements at low frequencies.An absorption threshold is seen at approximately 700 cm −1 . In the cobalt-doped material we see a superconducting gap in the conductivity spectrum with an absorption onset at 24 ± 2 cm −1 = 3.9±0.4kB Tc suggestive of weak to modera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…Usually the infrared ͑IR͒-active phonon frequencies are measured by IR ellipsometry. Windt et al 41 studied the IR and optical properties of LuNi 2 B 2 C and suggested weak to moderately strong coupling in this material. However, the IR-active phonon frequencies for these materials have not yet been determined experimentally and hence a theoretical study is highly relevant.…”
Section: Introductionmentioning
confidence: 99%
“…Usually the infrared ͑IR͒-active phonon frequencies are measured by IR ellipsometry. Windt et al 41 studied the IR and optical properties of LuNi 2 B 2 C and suggested weak to moderately strong coupling in this material. However, the IR-active phonon frequencies for these materials have not yet been determined experimentally and hence a theoretical study is highly relevant.…”
Section: Introductionmentioning
confidence: 99%
“…17, particularly͒. Our calculation suggests that there should be not too strong but clearly observable interband transitions at slightly different energies; 0.12 and 0.2 eV for YNi 2 B 2 C and 0.1 and 0.3 eV for LuNi 2 B 2 C ͑see the insets of Figs.…”
mentioning
confidence: 68%
“…There are several measurements of optical properties of rare-earth nickel borocarbide compounds. [13][14][15][16][17][18] The first experiments were mainly concerned with the relationship between the far-infrared ͑FIR͒ optical conductivity ͑OC͒ and the superconducting gap. A few of these experimental studies did obtain the interband optical absorption, however, there are quite large variations in the various reported experimental OC spectra.…”
mentioning
confidence: 99%